Activated iridium oxide film (AIROF) electrodes for neural tissue stimulation. (8th October 2020) - Frederick, Rebecca A; Meliane, I Yasmine; Joshi-Imre, Alexandra; Troyk, Philip R; Cogan, Stuart F
Abstract: Objective . Iridium oxide films are commonly used as a high charge-injection electrode material in neural devices. Yet, few studies have performed in-depth assessments of material performance versus film thickness, especially for films grown on three-dimensional (instead of planar) metal surfaces in neutral pH electrolyte solutions. Further, few studies have investigated the driving voltage requirements for constant-current stimulation using activated iridium oxide (AIROF) electrodes, which will be a key constraint for future use in wirelessly powered neural devices. Approach . In this study, iridium microwire probes were activated by repeated potential pulsing in room temperature phosphate buffered saline (pH 7.1–7.3). Electrochemical measurements were recorded in three different electrolyte conditions for probes with different geometric surface areas (GSAs) as the AIROF thickness was increased. Main results . Maintaining an anodic potential bias during the inter-pulse interval was required for AIROF electrodes to deliver charge levels considered necessary for neural stimulation. Potential pulsing for 100–200 cycles was sufficient to achieve charge injection levels of 2.5 mC cm −2 (50 nC/phase in a biphasic pulse) in PBS with 2000 µ m 2 iridium probes. Increasing the electrode surface area to 3000 µ m 2 and 4000 µ m 2 significantly increased charge-injection capacity, reduced the driving voltage required to deliver a fixed amount of charge, and reduced polarization of the electrodes during constant-current pulsing. Significance . This study establishes methods for choosing an activation protocol and a desired GSA for three-dimensional iridium electrodes suitable for neural tissue insertion and stimulation, and provides guidelines for evaluating electrochemical performance of AIROF using model saline solutions.